Clinicopathological Analysis of Hepatocellular Adenoma According to New Bordeaux Classification: Report of Eight Korean Cases - Kim, Hyunchul; Jang, Ja-June; Kim, Dong-Sik; Yeom, Beom Woo; Won, Nam Hee (Journal of pathology and translational medicine, 2013)
Hepatocellular adenoma (HCA) is a rare benign tumor of the liver. A subtype classification of HCA (hepatocyte nuclear factor 1α [HNF1α]-mutated, β-catenin-mutated HCA, inflammatory HCA, and unclassified HCA) has recently been established based on a single institutional review of a HCA series by the Bordeaux group. We used histologic and immunohistochemical parameters to classify and evaluate eight cases from our institution. We evaluated the new classification method and analyzed correlations between our results and those of other reports. Seven of our eight cases showed histologic and immunohistochemical results consistent with previous reports. However, one case showed overlapping histologic features, as previously described by the Bordeaux group. Four cases showed glutamine synthetase immunohistochemical staining inconsistent with their classification, indicating that glutamine synthetase staining may not be diagnostic for β-catenin-mutated HCA. HNF1α-mutated HCA may be indicated by the absence of liver fatty acid binding protein expression. Detection of amyloid A may indicate inflammatory HCA. HCA with no mutation in the HNF1α or β-catenin genes and no inflammatory protein expression is categorized as unclassified HCA. Although the new classification is now generally accepted, validation through follow-up studies is necessary.